Remesas internacionales sur-sur y norte-sur en Paraguay: patrones sociodemográficos, destino de los fondos y medios de circulación - Gómez, Pablo Sebastián (El Colegio de México A.C., 2016)
The analysis of international remittances in recipient countries is a widely debated issue in the specialized literature. However, there is no consensus in the various analytical and methodological perspectives over the direction, scope or implications of these processes. This article examines empirical evidence based on microdata from the permanent survey on Paraguayan households. It begins by comparatively analyzing the sociodemographic patterns of receiving and non-receiving households in the south and north. It subsequently details the mechanisms of the movement and use of international remittances in the various migratory circuits. The results highlight the specificities of the macro migratory systems linked to the global north and south.